Students' strategy preference moderates effects of open or focused self-explanation prompts on learning from video lectures - Zhang, Yi; Yang, Jiumin; Dai, Chenyan; Pi, Zhongling (Educational Technology ＆ Society, 2024)
Previous studies have shown that encouraging students to use self-explanation strategies has proven effective in text-focused learning contexts. However, no study to date has focused on how students' strategy preference moderates the effect of self-explanation strategies on learning from video lectures. The current study investigated how students' self-explanation strategy preference impacts their learning from video lectures by using prompts with a between-within-subjects design strategy preference (i.e., strategy preference vs. no strategy preference; between subject) and with prompt type (i.e., focused vs. open; within-subject), assessing learning performance, cognitive load, attention allocation, quantity and quality of explanation, and behavioral patterns. Study results showed that, compared to students using open prompts and with no self-explanation preference, providing focused prompts improved their learning performance and explanation quality, lowering their cognitive load and enabling them to search for information more accurately. Meanwhile, for students with a self-explanation preference, the two types of prompts used in this study had a similar positive impact on their learning performance and their quality of explanation.